HARDWARE AND SOFTWARE IMPLEMENTATION OF LIGHTWEIGHT CRYPTOGRAPHY ALGORITHMS - Zarif Khudoykulov (The Conference Hub, 2025)
Lightweight Cryptography (LWC) algorithms are critical for securing resource-constrained devices in the Internet of Things (IoT), embedded systems, and cyber-physical applications. This paper provides a comprehensive analysis of hardware and software implementations of LWC algorithms, focusing on the sequence of implementation, target platforms, programming languages, tools, and environments. We present key performance metrics, including area, power, throughput, and memory usage, and conduct comparative analyses of tools and performance data for NIST LWC ciphers, such as Ascon, GIFT-COFB, and TinyJAMBU. Insights from the NIST LWC standardization process highlight the trade-offs between security and efficiency. Our findings offer guidance for practitioners and researchers deploying LWC in constrained environments.
Keywords: Lightweight Cryptography, Hardware Implementation, Software Implementation, NIST LWC, IoT Security, Performance Metrics.